Gordon Brotherston: Book of the Fourth World: Reading the Native Americas Through their Literature - Michael, Ib (Tidsskriftet Antropologi, 2019)
Gordon Brotherston: Book of the Fourth World: Reading the Native Americas Through their Literature Anmeldes af Ib Michael